Readiness Analysis of Regional Innovation Implementation - Aminah, Sitti; Wardani, Dyah Kusuma (Research and Development Agency Ministry of Home Affairs, 2018)
The implementation of regional innovation has not been effective in improving public services and regional competitiveness. Several factors are considered to be an obstacle to implementing regional innovation, namely regulation, institutions, culture and leadership. The purpose of this study is to analyze the readiness of innovation support factors and also to analyze the relationship between these factors in the implementation of regional innovation. Data were collected by interviews and questionnaires distributed in July, August, and September 2016 in 7 (seven) Districts selected to represent HDI High areas, such as Palembang, Surakarta, Bandung and Batam and also represented Low HDI areas: Pesawaran, Bangkalan, and West Lombok. Data were analyzed by descriptive statistic and Pearson Correlation with SPSS ver.16 program. The results showed that the readiness of factors of factorization interpretation, regulatory readiness, leadership, innovation culture, and facilities and infrastructure were in high category, while the preparedness factor from the coordination and facilitation faced by stakeholders was also low category cooperation. The results show that all the factors supporting innovation except for facilitation and coordination in high HDI areas are superior to low HDI areas. The relationship between the supporting factors reveals that there are three types of relationships: very important, important, and not very important. Local innovation development strategies consist of core strategies and support strategies.